2007
DOI: 10.1021/jm061429p
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Potent Antimalarial Agents Based on Clotrimazole Scaffold:  Exploring an Innovative Pharmacophore

Abstract: Identification of new molecular scaffolds structurally unrelated to known antimalarials may represent a valid strategy to overcome resistance of P. falciparum (Pf) to currently available drugs. We describe herein the investigation of a new polycyclic pharmacophore, related to clotrimazole, to develop innovative antimalarial agents. This study allowed us to discover compounds characterized by a high in vitro potency, particularly against Pf CQ-resistant strains selectively targeting free heme, which are easy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 13 publications
3
41
0
Order By: Relevance
“…The latter had been synthesized based on the hypothesis that the imidazole ring would be able to coordinate with free heme and, consequently, to generate trityl radicals toxic to the parasite. 183 Hybrids 153 were found to inhibit several P. falciparum strains with IC 50 values ranging from 3.9 to 1371 nM. The results indicated that the 4-AQ ring substituents play an important role on the antimalarial activity, as the compounds bearing a chlorine atom at the C7 position generally displayed better activities than their analogues.…”
Section: Organometallic 4-aminoquinolinesmentioning
confidence: 99%
“…The latter had been synthesized based on the hypothesis that the imidazole ring would be able to coordinate with free heme and, consequently, to generate trityl radicals toxic to the parasite. 183 Hybrids 153 were found to inhibit several P. falciparum strains with IC 50 values ranging from 3.9 to 1371 nM. The results indicated that the 4-AQ ring substituents play an important role on the antimalarial activity, as the compounds bearing a chlorine atom at the C7 position generally displayed better activities than their analogues.…”
Section: Organometallic 4-aminoquinolinesmentioning
confidence: 99%
“…We have used the CLT scaffold to synthesize novel compounds that turned out to be very active against several Plasmodium strains in vitro and in vivo (17)(18)(19)(20). We report here a series of experiments conducted to evaluate the effects of several CLT analogues and related 4-aminoquinolines on the Ca 2ϩ -ATPase (SERCA1), revealing various degrees of inhibitory activity that were produced at relatively low concentrations by NF1442 (N-((3-chlorophenyl)(4-((4-(7-chloroquinolin-4-yl)piperazin-1-yl)methyl)phenyl)methyl)-7-chloro-4-aminoquinoline) and NF1058 (N-((3-chlorophenyl)(4-(pyrrolidin-1-ylmethyl) phenyl)methyl)-7-chloro-4-aminoquinoline).…”
Section: ؉ -Atpase Was Observed With Nf1442 (N-((3-chlorophenyl)(4-(mentioning
confidence: 99%
“…6 The antimalarial activity could also be modulated by varying the nature of the protonatable lateral chain. Substitution of the pyrrolidine group by a piperazine led to a moderate increase of antimalarial activity against asynchronous D10 and W2 strains (3d vs 3h and 4c vs 2).…”
Section: (C) Protonatable Lateral Chainmentioning
confidence: 99%
“…6 CLT is a well-known antimycotic drug which exhibits a weak in vitro antimalarial activity against different Pf strains and importantly, irrespective of their CQ sensitivity. 7,8 Biological activities of CLT are mediated by its ability to interact with ferri-protoporphyrin IX (Fe(III)-FP), which is present as the prosthetic group in several enzymes, such as (i) 14R-lanosteroldemethylase (14-LD), the fungal cytochrome inhibited by CLT, (ii) human P450 cytochromes, which are inhibited by CLT causing altered metabolism of both xenobiotics and endogenous presence of sodium hydride, to afford nitriles 25a and 25b, respectively, which were subsequently converted into the corresponding ketone derivatives 26a,b.…”
Section: Introductionmentioning
confidence: 99%